Impact of school support on cognitive engagement strategies in crisis contexts: dual pathways of academic motivation and psychological resilience - Wang, Mingjun; Xiong, Yuan; Wang, Meiliang (Frontiers in Psychology, 2026)
Educational disruption during emergencies presents substantial challenges to sustaining student engagement. This study investigates the mechanisms by which perceived school support influences cognitive engagement strategies, focusing on the mediating roles of academic motivation and psychological resilience. Data were collected from 693 secondary school students across 115 countries and analyzed using structural equation modeling. The analysis yielded three key findings. First, perceived school support significantly enhances both academic motivation and the use of cognitive engagement strategies. Second, psychological resilience—though not directly influenced by perceived school support—independently predicts academic motivation and cognitive engagement. Third, academic motivation serves as a core mediator between perceived school support and engagement, whereas the mediating role of psychological resilience was not statistically significant. These findings reveal a dual-pathway mechanism linking perceived school support to cognitive engagement and suggest a threshold effect of psychological resilience. The study contributes to the growing literature on education in emergencies by offering empirical evidence and actionable insights for the design of integrated support systems in post-crisis learning environments.